Implementation of the Ummi Method in Recognition of the Hijaiyyah Letters on Students of TKIT Nur Hikmah (Kindergarten) Bekasi during the Covid-19 Pandemic - Fattah Firdaus (Future Science, 2021)
Pandemic disease Covid-19 change many role of life. This involve many sector and unit in education, including kindergarten has to adapt a strategy during this situation. This study aims to determine how the implementation of the Ummi method in introducing hijaiyyah letters at the 4-5 years age students in TKIT Nur Hikmah on pandemic disease Covid-19. This study used a descriptive qualitative research approach in order to obtain broad and in-depth information about purpose of the study. The data source in this study were the principal of TKIT Nur Hikmah Bekasi, coordinator of Ummi method, competition teacher and parents of TKIT Nur Hikmah. The data collection used observation, interview, and documentation. The results showed that the implementation of the Ummi method in introducing the hijaiyyah letters in children on pandemic disease Covid-19 consisted of planning, implementation, evaluation and supervision. The use of the Ummi method provides a basic understanding of the hijaiyyah letters and the ease of distinguishing letters properly and correctly, both sequentially and randomly. The Ummi method on pandemic disease Covid-19 also has advantages, such as it is easy to understand and use, while the disadvantages are that it cannot be taught by uncertified Ummi method. In the Pandemic, the role of information technology and media becomes very important to connect between teachers and students. Teaching with the Ummi method will have a good impact on the child's future, because if the cultivation of Hijaiyyah learning is carried out early, where the letters are the letters used in the Al-Quran, it will have an impact on the behavior of children to have noble character.